A New Species of Hemilauxania Hennig (Lauxaniidae) from the Lower Eocene Oise Amber—The Oldest Record of Schizophora (Diptera)? - Jindřich Roháček; Christel Hoffeins (Insects, 2023)
Hemilauxania parvula sp. nov., a new fossil species of the family Lauxaniidae (Diptera: Acalyptratae), is described and illustrated from Oise amber, France (Eocene, lower Ypresian, ca 53 Ma), and its relationship is discussed. Inasmuch as this first finding of a member of Schizophora in Oise amber probably represents the oldest known record of this group of Diptera, the age of Schizophora, based on the known fossil records, is discussed.